Canon petrolero y la inversión pública en la Municipalidad Provincial de Maynas, periodo 2020 - Flores Pasmiño, Jose Manuel (2022)
The research is entitled "Oil Canon and Public Investment in the Provincial Municipality of Maynas Period 2020" and its general objective is to determine the relationship between the Oil Canon and public investment in the Provincial Municipality of Maynas period 2020. Our variables: Oil Canon as our independent or explanatory variable, Public Investment as dependent or explained variable. This research has as study period the year 2020, a year hit by the pandemic and that undoubtedly affects the results presented in this research. Through the theoretical framework we consolidate the importance of the oil canon and public investment. Both variables were analyzed to obtain individual results by obtaining, processing and analyzing the data with graphs and linear regression models with time series since we are dealing with data that is executed throughout the year of study, the results that were obtained showed that a variable such as the oil canon is significant and essential within the public investment budget for the district municipality of Maynas. However, the little or no execution of the oil canon did not dismantle the positive development of public investment in the province of Maynas. But it does show how the final execution of the planned budget for public investment slows down, which in general terms, insofar as its execution had an atypical behavior as a result of the pandemic that unraveled a result that, although it is worrying.